ICOS ATC/CAL Flask Release from Hyltemossa (150.0 m), 2020-03-24–2026-03-26 - Michal Heliasz; Tobias Biermann (Integrated Carbon Observation System, 2026)
can contain atmospheric composition data for any of a number of gases; the data can be a mole fraction, isotope ratio, or other related quantity
Heliasz, M., Biermann, T. (2026). ICOS ATC/CAL Flask Release from Hyltemossa (150.0 m), 2020-03-24–2026-03-26, ICOS RI, https://hdl.handle.net/11676/KvlTwa7dWw0sCTMfIS3nSZEc
Keywords: Atmosphere Thematic Centre; Flask; ICOS; time instant, UTC; time instant, UTC; CO2 (dry air mole fraction); CO2 (dry air mole fraction); standard deviation; standard deviation; number of points; number of points; quality flag; quality flag; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap